2005
DOI: 10.1161/01.str.0000149621.95215.ea
|View full text |Cite
|
Sign up to set email alerts
|

Dipyridamole for Preventing Recurrent Ischemic Stroke and Other Vascular Events

Abstract: on behalf of the Dipyridamole in Stroke Collaboration (DISC)Background and Purpose-Results from randomized controlled trials of dipyridamole, given with or without aspirin, for secondary prevention after ischemic stroke or transient ischemic attack (TIA) have given conflicting results. We performed a meta-analysis using individual patient data from relevant randomized controlled trials. Methods-Randomized controlled trials involving dipyridamole in patients with previous ischemic stroke or TIA were sought from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(46 citation statements)
references
References 22 publications
(23 reference statements)
1
43
0
2
Order By: Relevance
“…A pivotal study, ESPS-2 (European Stroke Prevention Study), showed that aspirin plus dipyridamole was significantly more effective than aspirin alone in secondary prevention of stroke (relative risk reduction 23.1%; p 0.006) and conveyed a similarly low risk of severe bleeding (1.6% vs 1.2%) 63) . Moreover, metaanalysis of 7 randomized trials was consistent with the ESPS-2 results 64) . ESPRIT (European/Australasian Stroke Prevention in Reversible Ischemia Trial) demonstrated that the incidence rate of the composite primary outcome (nonfatal MI, nonfatal stroke, vascular death, or major bleeding complication) was significantly lower in patients receiving aspirin plus dipyridamole than in those using aspirin alone (12.7% vs 15.7%, respectively; hazard ratio 0.80; 95% confidence interval 0.66-0.98) 65) ; however, aspirin plus dipyridamole was not superior to clopidogrel in the treatment of recurrent stroke in the recently completed PROFESS (Prevention Regimen for Effectively Avoiding Second Strokes) trial 66) .…”
Section: Phosphodiesterase Inhibitorssupporting
confidence: 78%
“…A pivotal study, ESPS-2 (European Stroke Prevention Study), showed that aspirin plus dipyridamole was significantly more effective than aspirin alone in secondary prevention of stroke (relative risk reduction 23.1%; p 0.006) and conveyed a similarly low risk of severe bleeding (1.6% vs 1.2%) 63) . Moreover, metaanalysis of 7 randomized trials was consistent with the ESPS-2 results 64) . ESPRIT (European/Australasian Stroke Prevention in Reversible Ischemia Trial) demonstrated that the incidence rate of the composite primary outcome (nonfatal MI, nonfatal stroke, vascular death, or major bleeding complication) was significantly lower in patients receiving aspirin plus dipyridamole than in those using aspirin alone (12.7% vs 15.7%, respectively; hazard ratio 0.80; 95% confidence interval 0.66-0.98) 65) ; however, aspirin plus dipyridamole was not superior to clopidogrel in the treatment of recurrent stroke in the recently completed PROFESS (Prevention Regimen for Effectively Avoiding Second Strokes) trial 66) .…”
Section: Phosphodiesterase Inhibitorssupporting
confidence: 78%
“…A meta-analysis based on a systematic review of all the available individual patient data from randomized controlled trials involving dipyridamole in patients with prior ischemic stroke or TIA confirms the additive effects of aspirin and dipyridamole [17]. Dipyridamole was compared with placebo, and combined aspirin and dipyridamole with the monotherapies and with placebo.…”
Section: Combined Mr-dipyridamole and Aspirin -Drug Evaluationmentioning
confidence: 92%
“…One trial found that amphetamine increased BP and HR in stroke, 30 important as hypertension is a major risk factor for further stroke, 31 and for a poor outcome. 32 Furthermore, no data exist on the effect of amphetamine on central or cerebral haemodynamic in this population, despite recent evidence that these parameters can be related to outcome in acute stroke. 33,34 We performed a phase II trial assessing the effect of amphetamine on motor function, and cerebral and cardiac haemodynamics.…”
Section: Introductionmentioning
confidence: 99%